CHALLENGES IN TEACHING & LEARNING PROFESSIONAL/BUSINESS COMMUNICATION IN TECHNICAL & PROFESSIONAL COURSES - Tiwari, Sarika Srivastava; Batra, J. C. (International Journal For Research In Business, Management And Accounting, 2018)
The ultimate aim of Technical & Professional Education is to impart Skills to the learners; to prepare them for their better future .One that opts for a professional degree aspires to be recruited in an esteemed organization. In an era of globalisation where every second person holds Technical/professional degrees the success mantras become more complicated, so it becomes extremely important to focus on an unavoidable ability that plays a vital role in the entire process of selection. In such an atmosphere where English language is broadening its compasses and taking the entire world into its sphere, Including Professional Communication as compulsory subject for all students pursuing Technical/ professional courses, to develop professional Skills has failed to reach desired outcome. Reason is Professional Communication classes in these courses are characterized by a poor attendance of learners and disinterestedness. The Faculties teaching this subject has to face enormous challenge. This paper is an attempt to come out with challenges faced by both faculty in teaching and learners in learning .At the end to reach at certain conclusion where these challenges could be overcome.